Inequality and Health: Is Housing Crowding the Link? - Maani, Sholeh A.; Vaithianathan, Rhema; Wolfe, Barbara (My University, 2007)
The authors propose a new mechanism through which income inequality can influence health. They argue that increased income inequality induces household crowding, which in turn leads to increased rates of infectious diseases.